STYLISTIC STUDY OF WAROK'S SPELLS OF PANARAGAN JAVANESE ETHNIC (KAJIAN STILISTIKA TERHADAP MANTRA WAROK ETNIK JAWA PANARAGAN) - Alip Sugianto (Leksema: Jurnal Bahasa dan Sastra, 2016)
This research aims at describing spell (mantra) language of Ponorogo’s warok on the aspect of language style, diction, and rhyme. This is a field research with Ponorogo’s warok as the informant. It applies observing, listening and note-taking technique. The data are analyzed using descriptive qualitative approach. The results of the research show that the spells of warok have characteristics of aliteration, assonance, polysidenton, asidenton, antonomatia, metaphor, hyperbole, pararhyme, and repetition language style, including anadiplosis, simploke, mesodiplosis, epizeuksis, tautotes, epistrofa, anafora. Meanwhile, on the aspect of diction, they cover connotation, denotation, religious symbols, synonyms, antonyms, and spirits. In addition, the taste of spell rhyme is resulted from some factors, such as sound repetition and connection between lines in a couplet, all that has functions to add artistic values to the spells so that they produce harmonious and synchronous effects of sounds.